Geochronology of the Cambrian: A Precise Middle Cambrian U-Pb Zircon Date from the German Margin of West Gondwana - E. Landing; G. Geyer; Buckwaldt, R.; Bowring, S. A. (Geological Magazine, 2015)
A volcanic tuff 1.0 m above the base of the Triebenreuth Formation in the Franconian Forest provides the first precise and biostratigraphically bracketed date within the traditional Middle Cambrian. The first illustration of fossils from the Triebenreuth Formation in this report and their discussion allow a more highly refined correlation within the Middle Cambrian. A weighted mean 206Pb–238U date of 503.14±0.13/0.25/0.59 Ma on zircons from this subaerial pyroclastic tuff was determined by U–Pb chemical abrasion isotope dilution mass spectrometry (CA-TIMS) techniques. At c. 6.0–7.0 Ma younger than the base of the traditional Middle Cambrian in Avalonia, the new West Gondwanan date from east-central Germany suggests that estimates of 500 Ma for the base of the traditional Upper Cambrian and 497 Ma on the base of the Furongian Series may prove to be too ‘old’. Biostratigraphically well-bracketed dates through most of the Middle Cambrian/Series 3 and below the upper Upper Cambrian/upper Furongian Series do not exist. An earlier determined 494.4±3.8 Ma date from the Southwell Group of Tasmania may actually prove to be a reasonable estimate for the age of the base of the traditional Upper Cambrian. Until high precision dates are determined on the base of the traditional Upper Cambrian and base of the Furongian Series, the rates of biotic replacements and geological developments and the durations of biotic zones in the Middle/Series 3 and Upper Cambrian/Furongian Series remain as ‘best guesses’.
Keywords: Germany; Middle Cambrian; Triebenreuth Formation; U–Pb zircon date